High reactivity of mesoporous CeO2 to dissociate chemical warfare agent sarin. (16th March 2023) - Li, Tianyu; Leonard, Matthew; Tsyshevsky, Roman; McEntee, Monica; Karwacki, Christopher; Durke, Erin M.; Kuklja, Maija M.; Rodriguez, Efrain E.
Abstract : Spectroscopic surface characterization under exposure of sarin gas (also known as GB) as well as DFT modeling reveals the high reactivity of mesoporous ceria (CeO2 ) towards sarin degradation. Abstract : We perform spectroscopic surface characterization on mesoporous ceria (CeO2 ) under exposure of sarin gas, also known as GB. We find mesoporous CeO2 displays extraordinary reactivity towards GB dissociation under high vacuum. The spectroscopic results combined with density functional theory (DFT) calculations suggest that the cleavage of the P–F and P–OR bonds are both possible pathways for GB to dissociate on the CeO2 surfaces. The modeling reveals differences in dissociation pathways of GB on the crystallographic (111)- and (110)-surfaces of ceria. We also report some dissociation of GB on mesoporous CeO2 under ambient conditions. The finding that mesoporous CeO2 can degrade GB under mild conditions is encouraging and implies the strong potential of ceria-based materials to be applied in combating chemical warfare agents related to the GB series.